Szaleńcy jako „odpady” nowoczesnego świata w kontekście wypowiedzi teoretyków kultury (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The thesis proves that the forms of medical treatment are determined by the culture in which sick people are functioning. It formsspecific disease entities and definite therapies. This is the culture that becomes principal for creating and functioning a medical system, and, in consequence, the system itself corresponds to its fundamental paradigms as far as the sphere of theory and practice is concerned.